Healthy Farm Index and biodiversity state in the moderate altitude region of Tabanan District, Indonesia - DWI PUTRA DARMAWAN; GEDE MEKSE KORRI ARISENA; NI WAYAN FEBRIANA UTAMI; NI LUH MADE INDAH MURDYANI DEWI; DESAK ASTHRI CAHYANI; NI MADE AYU VIONITA DEWI; NI KADEK PINGKAN WULANDARI; ARY BAKHTIAR; WEN WEN; ANIMESH K. GAIN; AYI PRIANA (Smujo International, 2026)
Abstract. Darmawan DP, Arisena GMK, Utami NWF, Dewi NLMIM, Cahyani DA, Dewi NMAV, Wulandari NKP, Bakhtiar A, Wen W, Gain AK, Priana A. 2026. Healthy Farm Index and biodiversity state in the moderate altitude region of Tabanan District, Indonesia. Asian J Agric 10 (2): g100210. https://doi.org/10.13057/asianjagric/g100210. Sustaining agricultural systems in tropical regions with complex topography is essential for enhancing productivity, resilience, and biodiversity conservation. This study applies the Healthy Farm Index (HFI) to evaluate farm-level sustainability across four dimensions production, biodiversity, ecosystem services, and quality of life in moderate-altitude agricultural landscapes of Penebel Sub-district, Tabanan District, Bali, Indonesia. Two villages with contrasting topographic conditions, Babahan and Senganan, were selected for comparative analysis. A total of 60 farming households and their associated farmlands were purposively sampled. Data collection included soil properties (pH and moisture), hardscape conditions, crop and livestock diversity, and farmer socio-economic characteristics. Biodiversity was assessed using the Shannon-Wiener Index, while relationships between HFI and other key indicators were analysed using linear regression and Pearson correlations in R. The results reveal that Babahan Village exhibited a higher median HFI (0.63) compared to Senganan Village (0.39), indicating more favorable agro-ecosystem conditions in relatively flatter terrain. A strong negative correlation was observed between soil pH and soil moisture (r = -0.98, p <0.001). Furthermore, species diversity (H′) showed a significant inverse relationship with HFI (R² = 0.76, p<0.001), suggesting a tradeoff whereby higher agricultural health scores are associated with the dominance of specific functional species rather than greater overall species richness. These findings highlight the influence of topography on farm-scale sustainability and underscore the critical role of land management practices. The study emphasises the need for site-specific strategies, including agroforestry and integrated water management, to optimise agricultural health in heterogeneous tropical landscapes.